Transformation of the Role Of OSIS as a Joyful Learning Agent in Strengthening Student Character at SMA Negeri 5 Samarinda - Mardatillah, Nur Isma; Herliah, Endang; Salamah, Alim; Pardosi, Jawatir (Journal of Educational Sciences, 2025)
This study aims to analyze the transformation of the role of OSIS as a joyful learning agent in supporting the strengthening of student character at SMA Negeri 5 Samarinda. In dealing with low student participation in OSIS activities, this organization is required to develop a fun learning approach to increase student motivation and involvement. This study uses a qualitative approach through observation, interview, and documentation methods which were carried out on April 12, 2025. Informants were selected purposively based on their active involvement in OSIS activities. The results of the study show that OSIS plays a strategic role in creating a conducive and fun learning environment through programs such as attribute checking, social services, creative wall magazines, and big events such as SMALAND. These programs are able to foster students' discipline, responsibility, leadership, empathy, and creativity. The discussion shows that the role of OSIS is not only administrative, but also as a driving force for learning that builds character through a collaborative and participatory approach. Support from the school is also a key factor in the success of implementing the role of OSIS in strengthening student character through joyful learning.